2018
DOI: 10.1080/20004508.2018.1514910
|View full text |Cite
|
Sign up to set email alerts
|

Professional formation and the final thesis in European teacher education: a fusion of academic and professional orientation

Abstract: This paper deals with possibilities and difficulties involved in the integration of academic and professional goals in two final thesis models in European teacher education, the thesis model and the portfolio model. The methodology used is a review of relevant research articles. The thesis model was identified in 19 articles and the portfolio model in 41 articles. Five dimensions were found to promote the integration of the two kinds of goals while four hamper this integration. The dimensions identified are si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
1
9
0
1
Order By: Relevance
“…Participants in this study provided a number of examples of how master's dissertation/thesis research work may facilitate teachers' practice and professional development. These seem also to support Råde's (2018) and Snoek et al's (2017) suggestions that the final degree projects by research may be considered as integrators or boundary crossers between academic and professional knowledge.…”
Section: Discussionsupporting
confidence: 71%
“…Participants in this study provided a number of examples of how master's dissertation/thesis research work may facilitate teachers' practice and professional development. These seem also to support Råde's (2018) and Snoek et al's (2017) suggestions that the final degree projects by research may be considered as integrators or boundary crossers between academic and professional knowledge.…”
Section: Discussionsupporting
confidence: 71%
“…The intended curriculum describes the purpose and value, the implemented curriculum is the teaching program as interpreted by its users, and the attained curriculum consists of learning experiences as perceived by learners (preservice teachers) and the resulting learning outcomes (Van den Akker, 2003). A (Toom et al, 2010) -Reflection on the process and outcomes of research and inquiry (Aspfors & Eklund, 2017;Dunn et al, 2008;Reis-Jorge, 2005;White et al, 2016) -Working in pairs, critical friends, or groups; communities of inquiry (Dobber et al, 2012 (Aspfors & Eklund, 2017;Dunn et al, 2008;Reis-Jorge, 2005;Toom et al, 2010;White et al, 2016) -Academic writing course (Munthe & Rogne, 2015;Råde, 2019) document analysis about the purpose and value of preservice teacher research showed a lack of constructive alignment (Biggs & Tang, 2011). Institutes for teacher education aim to develop an inquiry stance although the teaching activities and assessment forms are focused on research skills .…”
Section: Research Questionsmentioning
confidence: 99%
“…Despite these limitations, this study contributes to the existing body of knowledge on preservice teacher research and inquiry. Ample research on practitioner research and inquiry in various countries focuses on inservice teachers (e.g., Cochran-Smith & Lytle, 2009; Sachs, 2016), teacher educators (e.g., Jacobs et al, 2015; Tack & Vanderlinde, 2014), or preservice teachers in postgraduate programs (e.g., Aspfors & Eklund, 2017; Darling-Hammond, 2017; Råde, 2019; Toom et al, 2010). However, few studies focus on teaching preservice teacher inquiry competences to students in a professional bachelor’s degree program, such as in our context (e.g., Dunn et al, 2008; Munthe & Rogne, 2015).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sense, the student theses at the teacher education programmes are a balance act between the professional and academic discourse (Erixon Arreman & Erixon, 2017;Arneback et al, 2017). However, despite the presence of the teaching profession, the academic orientation (Råde, 2019) in the Swedish student thesis tradition is strong. When the student thesis became mandatory in Swedish teacher education in 1993 (Ministry of Education and Research, 1993:100), the intention was to make the education more research based (Bergqvist, 2000), in order to strengthen the teaching profession.…”
Section: Introductionmentioning
confidence: 99%